Improving Students' Learning Outcomes Through the Problem Based Learning Model to Present Prayer and Zikir In Daily Life at SMP Negeri 1 Sungai Kanan - Nurhalimah; Yudistira; Tambak, Yahya (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This study aims to improve student learning outcomes in Islamic religious education learning by using problem based learning. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that problem based learning can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.19%, the first cycle 76.87% and in the second cycle increased to 82.32%. Thus, the use of problem based learning can be used as an alternative to improve student learning outcomes in Islamic religious education learning.